Mesenteric mucinous cystadenoma: a diagnostic conundrum - Nidha Gaffoor; Archana Shetty; Aparna Muralidhar; N. Nagendra Prasad (Barpeta Obstetrics and Gynaecological Society, 2023)
Mucinous cystic neoplasms (MCNs) can be of ovarian or extra-ovarian origin. They share a common pathway of development, but pathogenesis remains controversial. Case reports involving the mesentery as a primary tumour site are few in literature. We report a case of a 48 year old female who presented with abdominal pain. Ultrasound revealed an intraabdominal cystic mass probably of adnexal in origin under radiology. On laparotomy, the mass was seen arising from the mesentery and was suspected to be a mesenteric cyst. On histopathological examination, the cyst was diagnosed to be of neoplastic nature (Mesenteric mucinous cystadenoma). MCNs of the mesentery remain asymptomatic until they attain a very large size. The awareness of this entity helps in considering this lesion in the differential diagnosis of mesenteric cysts. Complete surgical removal of the tumour without spillage is recommended, due to higher risk of recurrence and malignant transformation. The definitive diagnosis is based on histopathological examination which can exclude a borderline or malignant component, thereby helping in better patient management.